DO INFORMED INVESTORS PREFER FUTURES? - Shikha Singh, Shailesh Rastogi, Venkata Mrudula Bhimavarapu (International Journal of Modern Agriculture, 2020)
In today’s day and age, trading in the stock market has become more dynamic and flexible owing to the variability that is being offered within domains such as that within derivatives. Derivatives offer some good risk-management tools in the form of futures and options which not only helps in transferring risk to those are prepared to own risk but also generate returns at high volatile situations. Naturally, with the increasing volatile trading, informed investors play a vital part & traders has grown leaps and bounds. In this study, we try to understand the impact of the preference towards futures by the informed traders, the same way they show an unbound inclination towards the options which the literature suggests. This study takes the data from Nifty-50 index into the consideration between the period Jan 2016 to Dec 2017 and utilizes the volatility of the spot prices by applying the GARCH model. Using regression analysis, the paper presents the evidence which indicates that informed investors do prefer futures over spot market.